Developing Islamic Organizational Communication in the Digital Era: A Systematic Literature Review Approach - Nona Khairiah; Syukur Kholil (Journal Analytica Islamica, 2025)
Digital transformation has fundamentally changed the way organizations communicate, including in the context of Islamic value-based organizations. Islamic organizational communication faces the challenge of remaining technologically relevant without losing its ethical and spiritual dimensions. This study aims to synthesize various academic findings on Islamic organizational communication in the digital era using the Systematic Literature Review (SLR) approach. Data were collected from 1,000 scientific publications in the last five years through the Publish or Perish application , then analyzed using the VOSviewer bibliometric tool to identify thematic patterns, temporal dynamics, and concept density. The findings show that the literature is concentrated on two main poles: structural-managerial aspects and digital da'wah communication. However, there is still fragmentation of studies and the absence of a conceptual model that systematically integrates Islamic values in digital organizational communication. This study uses two main theoretical frameworks: Cultural Approach to Organizations and Systems Theory in Organizational Communication , which together explain how Islamic communication can be seen as a system of values and symbols that are adaptive to environmental changes. The contribution of this research lies in providing a scientific synthesis that not only enriches academic discourse but also becomes a practical basis for the development of contextual, ethical, and sustainable Islamic communication strategies in the digital era. These findings are expected to be a basis for further research and the formulation of organizational communication policies based on Islamic values that are relevant to the challenges of the times.